Industry 4.0 Powered Process Technology Innovation, Firm’s Leanness, and Eco-Environmental Performance During the COVID-19 Phase - Sun, Han; Chu, Xiao (Frontiers in Environmental Science, 2022)
Amid rising market competitiveness, Industry Revolution (IR) 4.0 oriented technological integration is considered an imperative driver of sustainable organizational performances and green supply chain management. This study explores the role of IR 4.0 powered process technology innovation in enhancing Leanness, Green Supply Chain Management, and Organizational Performance (including operational, economic, and environmental) during COVID-19. For this purpose, a novel conceptual framework was developed, and Partial Least Square-Structural Equation Modelling (PLSM) was employed on primary data of 314 respondents collected from Chinese manufacturing industries. Moreover, Multi-Group Analysis was also implemented to compare firms’ willingness to implement IR 4.0 technologies powered process innovation. The results exhibit that Green IR 4.0 powered process technology innovation improves firm’s leanness and stimulates environmental, optional, and economic performances. Similar findings are endorsed through the green supply chain management channel. Manifestly, COVID-19 instigated firms to adopt IR 4.0-based technological processes for efficient supply chain management. Based on these results, organizations are recommended to integrate IR 4.0 induced technology innovation to spur manufacturing firms’ eco-economic and operational performance.